Analysis of glycosuria in okapi (Okapia johnstoni): Examination of urinary N‐acetyl‐β‐D‐glucosaminidase. (19th May 2014) - Kawasaki, Ryuta; Azumano, Akinori; Ueda, Miya; Tanaka, Souhei; Yokota, Aya; Katoh, Kazuo; Hagino, Akihiko
Abstract We analyzed the urinary excretion of glucose and N‐acetyl‐β‐D‐glucosaminidase (NAG) in six okapis (Okapia johnstoni) in captivity to investigate the cause of their urinary sugar excretion. The urinary glucose‐positive okapi had significantly higher urinary NAG indices than the urinary glucose‐negative okapi. There was also a positive correlation between urinary glucose levels and urinary NAG indices. These results suggest that the proximal tubular function of the glycosuric okapi may have been obstructed, which impaired glucose reabsorption.